A framework for design methods, models and techniques for product and process development: A novel classification to increase their applicability in practices. Issue 7 (14th October 2019) - Sanhueza, Karen Scarlette; Nikulin, Christopher
Abstract : Purpose: The purpose of this paper is to address the emerging need to map knowledge and information with a novel classification, suitable to have a clear and integrated overview of the design method, models and techniques from both the sides of product and process. The proposed classification allows to understand main relevance of different design methods, models and techniques according their characteristic and also level in where company usually applied. Design/methodology/approach: The authors decided to structure the research into three steps: from the analysis of background literature, in order to draw the main evidences for the development of a novel classification, to their application. First, the papers search related to collect the different methods used in literature. Second, paper characterization which aims to understand main traits and usefulness of design methods, models and tools. Third, the assessment of design methods, models and tools according proposed classification. Findings: Each method, model or technique would be more useful according to the context in which is applied. Most of methods and modes can be continuously improving, considering different sub-classification or complement each other, striving to compensate to the extent possible for weakness in any one of the approaches. Research limitations/implications: The proposed classification did not deliver absolute results in every analyzed model or techniques, it delivered a wide range of possibilities in every sub-classification, thus the engineers get multiple options to choose depending on its main goal or the available resources. Originality/value: The author's proposal aims at filling a classification gap in the design method literature, which has to plausible in use. The different alternatives can be represented according to a scalable and hierarchical logic embedding also a more structured evaluation of the methods and tools in practice.